Стратегічна адаптація товарної політики підприємств в умовах цифрової трансформації ринків споживчих товарів - Райко, Діана Валеріївна (Видавничий дім "Гельветика", 2026)
Стаття присвячена дослідженню механізмів стратегічної адаптації товарної політики підприємств в умовах цифрової трансформації ринків споживчих товарів. Розглянуто поточні теоретичні підходи до формування та стратегічного управління товарною політикою фірм у цифровому просторі. Вивчено тренди цифровізації ринку споживчих товарів та її відбиток на поведінці покупців і складовій ринкового попиту. З'ясовано вплив цифрових технологій на розпорядження асортиментом, життєвим циклом товарів та їхнє позиціонування на ринку. Проаналізовано міжнародний та вітчизняний досвід адаптації товарної політики підприємств у цифрових умовах та ідентифікувати успішні моделі. Розроблено рекомендації щодо стратегічної адаптації товарної політики підприємств із використанням цифрових інструментів і аналітики споживчого попиту. Запропоновано механізми оцінки ефективності впровадження цифрових інструментів у товарну політику та моніторингу досягнення стратегічних цілей.

Strategic adjustment of the product policy of organizations in the environment of digital transformation of consumer goods markets" is due to swift shifts in consumer demand and the proliferation of digital technologies in all facets of business. Under contemporary circumstances, entities are compelled to promptly modify product plans to sustain competitive strengths and enhance the effectiveness of administrative choices. This paper focuses on examining methods for strategic adjustment of the product strategy for businesses amid the digital reshaping of consumer goods markets. It looks into current trends in market digitization, shifts in buyer conduct, and the effect of digital tools on shaping product range, item placement, and managing their overall existence. The objective of the piece is to explore the main directions of digital change in consumer goods sectors and formulate well-founded advice and plans for revising enterprise product stances, thus securing their rivalry, capable oversight of stock and product lifecycles, and improving interactions with customers through digital means and demand observation. To attain the article's objective and complete the assigned duties, a range of scholarly techniques were utilized: examination of academic and specialized publications, contrasting evaluation of local and global practices, content review of online platforms and promotional messaging, simulation, and crafting of strategic adjustment projections. Current theoretical avenues for establishing and strategically overseeing the product direction of firms in the digital sphere are examined. The shifts in digital reshaping of the consumer goods sector and its effect on purchaser conduct and the makeup of market need were investigated. The effect of digital innovations on handling the range, product lifespan, and their placement in the marketplace was established. The global and local practice of adjusting the offering strategy of firms under digital circumstances was examined, and effective patterns were pinpointed. Suggestions were formulated for the strategic adjustment of the product strategy of enterprises employing digital instruments and customer preference data. Furthermore, the suggested methods for tracking KPIs and evaluating the success of digital solution deployment can be utilized by executives to organize and fine-tune business procedures instantly.
Strategic adaptation of the product policy of enterprises in the conditions of digital transformation of consumer goods markets
Keywords: товарна політика; цифрове середовище; цифрові платформи; ринок споживчих товарів; асортимент; персоналізація; гнучкість асортиментного планування; стратегічна адаптація; product policy; digital environment; digital platforms; consumer goods market; assortment; personalization; flexibility of assortment planning; strategic adaptation